Experimental study of circular hollow reinforced concrete column strengthened with partial Carbon Fibre Reinforced Polymer (CFRP) confinement. (October 2019) - Ismail, R; Rashid, R S M; Zakwan, F A A; Hejazi, F
Abstract: Structural strengthening with Carbon Fibre Reinforced Polymer (CFRP) confinement has been widely used in civil engineering applications. However, the use of CFRP has always triggered environmental and sustainable issues due to its hazardous manufacturing and disposal process. By using partial CFRP confinement, the use of CFRP as the strengthening material could be reduced. The circular hollow reinforced concrete column is commonly used in seismic zones due to its self-weight reduction and better structural efficiency of strength/mass and stiffness/mass ratios properties. However, up until today, the understanding of circular hollow reinforced concrete column behaviour still lacks, especially with CFRP partial strengthening confinement. Therefore, this paper is testing a 6 full-scale circular hollow reinforced concrete columns with 2 m height, 250 mm of outer diameter, and 110 mm of inner diameter. The behaviour of the unconfined circular hollow column will be compared with partial CFRP confinement under axial load. The circular hollow reinforced concrete column with partial CFRP confinement is proven to be able to strengthen circular hollow column effectively through this study.